Effect of moderating factors on value relevance of earnings information among pyramid structure firms in selected ASEAN countries - Mohamad Anwar, Nazratul Aina (2010)
The objective of this study is to ascertain if the presence of institutional owner as second largest owner, the absence of CEO duality and the higher level of cash flow rights in the hand of ultimate owner, hereby referred to as moderating factors, help to improve the value relevance of earnings information in pyramid structure firms. The separation of cash flow rights and control rights in pyramid structure firms has entrenched the ultimate owner and provide them with opportunities to manipulate earnings information, which in turn reduce the value relevance of the earnings information reported. This study hypothesizes that the moderating factors identified will help to reduce the agency problem between ultimate owner and minority shareholder by reducing the opportunity of ultimate owner to manipulate earnings information, which in tum will increase the value relevance of earnings information in pyramid structure firms. The sample in this study consists of 153 pyramid structure firms from Malaysia, Indonesia, Thailand and Philippines, where the identity of the ultimate owner is family ownership and the firms were originally assembled by Claessens et al. (2002) from 1992 to1997. Earnings-return model with the interaction between earnings information reported by pyramid structure firms and moderating factors is provided to show the effect of the factors on the earnings-return relationship in an attempt to measure the value relevance of earnings information reported. Positive earnings-return relationship and higher R2 indicate that the earnings information is value relevant and vice versa. Using panel data regression, the results show that the presence of all proposed moderating factors is significant to minimize and mitigate the negative effects of the structure based on higher R2 reported with positive earnings-return relationship. Thus, the moderating factors moderate the negative effects of pyramid structure firms and help to increase the low value relevance of earnings information among pyramid structure firms.